Ei pelkästään "vapaudenprenikoita" – sota-ajan erikoisempia kunniakirjoja ja -merkkejä - Kauhanen Riku (Sotilasperinteen seura, 2022)
Not just Crosses of Liberty – Curious honors and medals from the times of war
During the Winter War (1939–1940), Interim Peace (1940–1941) and Continuation War (1941–1944) hundreds of thousands of honors were given to Finnish soldiers and civilians as a sing of gratitude and distinguishing and as memories. Also, special medals and crosses, that were not awarded by the state or army were given in some occasions. These decorations are numerous but not well studied. Decorations and information about them have survived haphazardly. Some Finnish museums and archives have honors in their collections, but it is more likely to find them in online auctions. As the generations that have faced the war are passing away, so is the knowledge and context of these honors.
Honors made of paper were cheap and a quick way to thank participants in collection competitions such as collections of junk, metal, paper or rags for industry. Honors were given to individuals, farmsteads, teams, schools and administrative boroughs for accomplishments and acknowledgments: for example, farms which fulfilled their provisions requisitions were given honors. Also, some specially made medals and crosses were given. Some units which were created at the end of Winter War or were disbanded during the Continuation War received little or no public honors, but the units themselves might have created honor of their own. Some medals were even created during the war by individual parties purely for financial profit and as “trench humor”, such as the “Anti-bedbug association“ in Terijoki in 1943 with it’s own honor and honorary cross.
Most honors were given to winners of sport events and other competitions. Many “trench art masters”, who made excellent pieces of trench art were given honors which stated this title after successful contests and exhibitions. Some trench art artefacts were also given as prizes in competitions. Some curious challenge cups, not ordinary trophies, were given to military units and organizations. For example the 1. Anti-aircraft Defence Regiment stationed in Helsinki received a 1:5 scale model of a 20 mm AA-gun from German Gustlow-Werke company to be used as a challenge cup.
These decorations are interesting in many ways and deserve a closer study and preservation for future generations. Some honors and perhaps even medals were designed and drawn by famous Finnish artists. Even though most papery honors were simple in design some documents were beautifully decorated, especially the honors given to the young and children. Study of these honors might reveal “forgotten” pieces from Finnish artists. It should be noted that many subjects of honors and other decorations are current: fitness, recycling and collection of natural products are all important and trending subjects these days and were worth many honors during the war. Subjects of these honors create bridges to modern era and give us deeper sense and purpose of these matters.
Tahtoa ja terästä: näkökulmia sotilasperinteeseen IV